Parental Child-Rearing Styles and Subjective Well-Being of Children Involved in Bullying - Ihsana Sabriani Borualogo; Ferran Casas (Psympathic : Jurnal Ilmiah Psikologi, 2021)
This study aims to examine how parental child-rearing styles contribute to subjective well-being of three groups: bullying victims, bullying perpetrator-victims, and those uninvolved in bullying. These groups were categorized based on the children’s self-reported bullying incidents. This study used quantitative approach with cross-sectional design. The participants were 781 4th to 6th-grader students (51.98% boys, 48.02% girls), consists of 329 bullying victims, 197 were both bullying perpetrators and victims, and 255 were uninvolved in bullying. Parental child-rearing styles were measured using The Egna Minnen Beträffande Uppfostran for Children (EMBU-C), while subjective well-being was measured using the Children’s Worlds Subjective Well-Being Scale 5 items (CW-SWBS5). Data were analysed using structural equation modelling. The results revealed that the warmth of fathers and mothers made significant and direct contributions to the subjective well-being of children uninvolved in bullying, where the father’s warmth negatively contributed, while the mother’s warmth positively contributed. Similar results did not appear in the subjective well-being of victims or perpetrator-victims.